2002
DOI: 10.1523/jneurosci.22-02-00478.2002
|View full text |Cite
|
Sign up to set email alerts
|

ERK MAP Kinase Activation in Superficial Spinal Cord Neurons Induces Prodynorphin and NK-1 Upregulation and Contributes to Persistent Inflammatory Pain Hypersensitivity

Abstract: Activation of ERK (extracellular signal-regulated kinase) MAP (mitogen-activated protein) kinase in dorsal horn neurons of the spinal cord by peripheral noxious stimulation contributes to short-term pain hypersensitivity. We investigated ERK activation by peripheral inflammation and its involvement in regulating gene expression in the spinal cord and in contributing to inflammatory pain hypersensitivity. Injection of complete Freund's adjuvant (CFA) into a hindpaw produced a persistent inflammation and a susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
374
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 413 publications
(410 citation statements)
references
References 63 publications
(89 reference statements)
34
374
1
1
Order By: Relevance
“…Involvement of ERK and c-fos after estrogen replacement in ovariectomized CFA rats ERK is one member of the mitogen-activated protein kinase (MAPK) family, which is known to have different functions in sensory processing [33][34][35]. In the present study, the expressions of ERKand c-fosin the sham, OVX, and estrogen-treated CFArats were investigated.…”
Section: Estrogen Replacement Reversed the Decrease Of Pwt In Ovariecmentioning
confidence: 91%
“…Involvement of ERK and c-fos after estrogen replacement in ovariectomized CFA rats ERK is one member of the mitogen-activated protein kinase (MAPK) family, which is known to have different functions in sensory processing [33][34][35]. In the present study, the expressions of ERKand c-fosin the sham, OVX, and estrogen-treated CFArats were investigated.…”
Section: Estrogen Replacement Reversed the Decrease Of Pwt In Ovariecmentioning
confidence: 91%
“…Animals were killed quickly in a CO 2 chamber. The L5 dorsal horns were removed rapidly and homogenized in an SDS sample buffer that contained a mixture of proteinase and phosphatase inhibitors (Ji et al, 2002a). The protein concentration of tissue lysates was determined with a BCA Protein Assay Kit (Pierce, Rockford, IL), and 30 g of protein was loaded in each lane.…”
Section: Methodsmentioning
confidence: 99%
“…ERK and p38 both have distinct roles in generating pain sensitivity. Activation of ERK in dorsal root ganglion (DRG) and dorsal horn neurons contributes to the development and maintenance of pain hypersensitivity through transcription-dependent and -independent means (Ji et al, 1999(Ji et al, , 2002aAley et al, 2001;Karim et al, 2001;Dai et al, 2002). p38 has been implicated in exaggerated pain states (Watkins et al, 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of Trk receptors in turn initiates downstream cascades, including activation of MAPK (Encinas et al, 1999;Hagemann and Blank, 2001). Activation of MAPK enhances gene expression for a variety of protein elements (Gegelashvili et al, 1997;Hagemann and Blank, 2001;Williams et al, 2001;Ji et al, 2002) and indeed has been shown to induce the expression of both GLT-1 mRNA and protein in astrocytes (Gegelashvili et al, 2000;Zelenaia et al, 2000). Thus the Trk receptor and MAPK pathway may participate in GT upregulation in CCI rats.…”
Section: Possible Mechanisms Of Gt Changes After CCImentioning
confidence: 98%